2017
DOI: 10.1111/jfpp.13334
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of electron beam irradiation for microbial decontamination of turmeric powder (Curcuma longaLinne) and analysis of curcuminoid degradation

Abstract: The effectiveness of electron beam (EB) disinfection and sterilization technology when applied to turmeric powder (Curcuma longa Linne) was investigated. The bacteria in turmeric powder were sensitive to EB irradiation. From an initial turmeric aerobic bacterial count of 10 7 colony-forming units per gram (cfu/g), a microbial contamination level of below 1.0 3 10 3 cfu/g was obtained atan absorbed dose of more than 7 kGy EB irradiation. EB irradiation at 10 kGy gave a contamination level of less than 10 cfu/g … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
(21 reference statements)
0
5
0
Order By: Relevance
“…Gumus () also reported that the antifungal activities of spice and herb extracts were increased by irradiation at low doses (1.2 kGy) but decreased by higher doses (3–5.1 kGy). Conversely, Yamaoki and Kimura () found very little degradation of curcuminoids at the dose sufficient for microbial decontamination in turmeric powder.…”
Section: Introductionmentioning
confidence: 99%
“…Gumus () also reported that the antifungal activities of spice and herb extracts were increased by irradiation at low doses (1.2 kGy) but decreased by higher doses (3–5.1 kGy). Conversely, Yamaoki and Kimura () found very little degradation of curcuminoids at the dose sufficient for microbial decontamination in turmeric powder.…”
Section: Introductionmentioning
confidence: 99%
“…To date, a single study has employed e-beam technology for sterilizing turmeric, utilizing doses spanning from 5 to 30 kGy [ 29 ]. The authors investigated the impact of these doses on the elimination of specific bacteria, the extraction of turmeric components, and the radiolysis of curcuminoids utilizing the high-performance liquid chromatography (HPLC) method.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we aimed to study the application of ionizing radiation to crude drugs and crude drug preparations as a countermeasure against microorganism contamination [8,9]. Many studies on the chemical and microbial qualities of irradiated herbs or medicinal plants have been reported [10][11][12].…”
Section: Introductionmentioning
confidence: 99%